Leadless cardiac pacing in resource limited settings: A Groote Schuur hospital experience with the Micra leadless pacemaker - Mkoko, P.; Govender, K.L.; Gouws, B.V.R.; Chin, A. (SA Heart Journal, 2020)
Background: Cardiac pacemakers improve survival and quality of life in patients with atrioventricular (AV) block. However, conventional pacemakers carry a small risk of both acute and chronic lead and pacemaker generator complications. Leadless pacemakers negate these risks by not having a pacing lead and a subcutaneous generator. We report our Groote Schuur Hospital experience with the Medtronic Micra transcatheter pacing system (TPS). Methods: We report a consecutive case series of patients that received the Micra leadless pacemaker. The Micra transcatheter pacemaker, a single chamber ventricular pacemaker, is inserted using a TPS via the femoral vein into the right ventricle. Implantation data were obtained, and medical records were reviewed for the 6 weeks and 1-year follow-up visits. Results: A total of 5 patients were implanted with a Micra leadless pacemaker from 11 March 2015 - 2 November 2016. Four patients were male and 1 female, with an average age of 64 years. Four patients received the pacemaker for a second- or third-degree AV block and 1 patient received the pacemaker for unexplained syncope and right bundle branch block. The Micra leadless pacemaker was successfully implanted in all patients with no acute implantationrelated complications. One-year follow-up was available for 4 patients with good pacing thresholds, sensitivity and impedance. One patient demised after 9 months post Micra implantation due to unrelated causes (acute myeloid leukaemia). Conclusion: The Micra leadless pacing system is safe and effective and shows good short-term results in a real-world, resource-limited setting. This form of pacing offers a viable option for patients who require pacing for AV block, especially in patients with vascular access problems or who are at high risk of lead or pacemaker generator complications.